Predicting mobile network operators users m-payment intention - Leong, Choi Meng; Tan, Kim Lim; Puah, Chin Hong; Chong, Shyh Ming (Emerald Publishing Limited, 2020)
Purpose – This study aims to investigate the intention of using mobile payment (m-payment) services in Sarawak, Malaysia. Design/methodology/approach – A total of 194 online payment users were selected to respond to the structured questionnaire. The partial least squares-structural equation modelling (PLS-SEM) was used to analyse the data by assessing the measurement and model. Findings – Perceived usefulness(PU)and perceived ease of use mediated the relationship between perceived compatibility(PC) and the intention to use the mobile payment for mobile network operators’ services. Research limitations/implications – The analysis provides insights that PC is considered as a signiﬁcant determinant for mobile payment of mobile network operators’ services. Practical implications – The operators can consider factors such as PC in the design of their mobile applications and the potential to expand them-payment services too theirs e-wallet such as Sarawak e-wallet. The model possesses medium prediction power, which suggests that other variables such as perceived security and personal innovativeness also can be used to predict the usage behavior of mobile payment for the mobile network services. Originality/value – The present study contributes to them-payment users’ behavior intention literature by investigating the mobile-based predictors of using m-payment technology in an emerging digital economy state in Sarawak, Malaysia. This study also extends the knowledge of technology acceptance model by introducing the mediation effect of PU and ease of use between the mobile-based predictors and m-payment intention.